Spousal separation, selectivity and contextual effects: exploring the relationship between international labour migration and fertility in post-Soviet Tajikistan - David Clifford (Demographic Research, 2009)
This paper contributes to the sparse literature on the impact of temporary migration on fertility in origin areas. It examines the case of male labour migration from post-Soviet Tajikistan, a significant and relatively recent phenomenon. Fertility and migration models are solved simultaneously to account for cross-process correlation. There is clear evidence for a short-term disruptive effect of spousal separation, but it is too early to assess the implications for completed fertility. While there is no evidence for unobserved selectivity at the couple level, there is a significant positive correlation between the migration and fertility processes at the community level.